Adaptation of the "in-gel release method" to N-glycome analysis of low-milligram amounts of material - Rendić, Dubravko; Wilson, Iain B. H.; Lubec, Gert; Gutternigg, Martin; Altmann, Friedrich; Léonard, Renaud (Electrophoresis, 2007)
Protein N‐glycosylation is a post‐translational modification which plays numerous crucial physiological roles. The N‐glycan pattern varies depending on the species organs, tissues and even cell types and their respective physiological states. Obtaining enough starting material from a particular cell type or tissue for N‐glycan purification by conventional methods can, in certain cases, be very difficult. Previously, a sensitive technique, the “in‐gel release method” that allows the determination of N‐glycans attached to a protein isolated by SDS‐PAGE, has been developed in this and other laboratories. Here, we describe the adaptation of this method to obtain information on the N‐glycome from minute amounts of tissue. The starting material, ranging from less than a milligram to a few milligrams of fresh tissue, is directly ground in Laemmli sample buffer and subject briefly to discontinuous Tris–glycine–SDS‐PAGE. The Coomassie‐stained band containing the majority of the proteins is subject to the “in‐gel release method”. The developed technique was used to analyze N‐glycan patterns of different samples from Caenorhabditis elegans, Drosophila melanogaster, Spodoptera frugiperda, Trichoplusia ni, Nicotiana benthamiana, Arabidopsis thaliana, and Mus musculus. Furthermore, the technique was used to determine the effects of transient small‐scale RNAi‐mediated knock‐down of a glycosylation‐related gene in Drosophila Schneider 2 cell line.